Single Dose Silodosin Prior to Voiding Cystourethrogram: A Pharmacological Adjunct to Enhance Visualization of Posterior Urethra - Nagathan, Deepak Sharanappa; Dalela, Divakar; Sankhwar, Satyanarayan; Goel, Apul; Dwivedi, Amod Kumar; Yadav, Rahul (Urology Journal, 2014)
Abstract Voiding cystourethrogram (VCUG) is needed to ascertain the upper end of urethral stricture. Occasionally, a patient is unable to open the bladder neck with resultant failure of the test. Realizing the strong and prompt alpha antagonistic action of silodosin, we evaluated single 8 mg dose as a pharmacological adjunct prior to VCUG to overcome this problem.